Related-key impossible differential attack on a lightweight block cipher MIBS - Ping CHEN; Fu-cheng LIAO; Hong-ru WEI (Tongxin xuebao)
The strength of MIBS algorithm against the related-key impossible differential attack was examined. MIBS is a lightweight block cipher algorithm. By using the key-expanding properties of MIBS-80 algorithm, a related-key differ-ential feature was presented and a 10-round impossible differential method was constructed by combining special ci-pher-plaintexts. Based on the impossible differential method, an attack to 14-round MIBS-80 algorithm was given, and the attack complexity both on data and on time were gained. Analysis results indicate the attack to MIBS of 14 rounds MIBS-80 algorithm needs 254chosen plaintext operations and 256encrypting computations.